157k views
5 votes
Evaluate (3)^1/6 × (3)^-2/3

User Brana
by
5.4k points

2 Answers

9 votes
39918656718818881883
User Sob
by
4.8k points
11 votes

Answer:


(1)/(√(3))

Explanation:

Evaluate:
3^{(1)/(6)} * 3^{-(2)/(3)}

Apply exponent rule:
a^b * a^c=a^(b+c)


\begin{aligned} \implies 3^{(1)/(6)} * 3^{-(2)/(3)}&=3^{(1)/(6)-(2)/(3)}\\ &=3^{-(1)/(2)\end{aligned}

Apply exponent rule:
a^(-n)=(1)/(a^n)


\implies 3^{-(1)/(2)}=\frac{1}{3^{(1)/(2)}}=(1)/(√(3))

User Etham
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.